Language of the forestry discursive community (based on the traditional culture of the Urals) - O. A. Teusch (Дискурс профессиональной коммуникации, 2020)
The article is devoted to the peculiarities of the discursive field “Forestry activity in the Urals”. The relevance of the study is determined by the increased attention of modern linguistics to the problems of regional specificity of professional discourse, the development of which is at the initial stage. The aim of the article is the etymological and onomasiological description of the units of the discursive field, characterized as “Forestry activity in the Urals”. Semasiological, onomasiological methods and the method of scientific description are used to achieve this goal. Lexical units included in the field are identified, their origin is interpreted. The main field segments are defined. As a result of the analysis of the empirical material belonging to the “Forestry activity in the Urals” discursive field, it was revealed that in the Ural regional lexical system a specific system of concepts was developed. It has been implemented in the speech activity of dialect speakers. The Ural General dialect foundation is the basis for the modern professional communication of foresters and timber producers of the region.